ANALISIS AKUNTABILITAS PUBLIK PADA KABUPATEN/KOTA PEMERINTAH INDONESIA - Meilisa, Mulya; Fadli, Fadli (ITB AAS Indonesia Surakarta, 2024)
This research aims to test and analyze public accountability analysis in Indonesian government districts/cities using a sampling technique, namely total sampling (census) in which the entire population is used as a sample. This research uses a quantitative approach. The data collection method in this research uses secondary data obtained from Regional Government Financial Reports (LKPD) sourced from BPK PPID and SAKIP Scores from LAKIP which are processed by the Ministry of Pan and RB-RI. The data analysis technique uses multiple linear regression analysis with the help of the SPSS program. The results of this research show that (1) weaknesses in the internal control system have a negative effect on the quality of public accountability, (2) audit findings have no effect on the quality of public accountability, (3) total expenditure has a positive effect on the quality of public accountability.